Pewarisan Sifat Agronomi Tanaman Cabai (Capsicum annuum L.) Toleran di Lahan Gambut - Zainal Arifin; Gunawan Tabrani; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT Plant breeding programs aimed to increase the production through creating new chili hybrid. The genetic parameters information which is also known as genetic variability and heritability should be know before start the selection. Research aimed to identify the agronomic trait inheritance of chili as selection criteria that tolerance in peatlands. The experiment was conducted in peatlands Rimbo Panjang village, Kampar Regency. The experiment lasted from November 2012 to April 2013. Research was arranged experimentally using Randomized Block Design (RBD) consists of seven genotypes of chili that IPB C- 5, IPB C- 111, 1PB C- 120, IPB C- 159, IPB C- 159 x IPB C- 5, IPB C- 159 x IPB C- 111 and IPB C- 159 x IPB C- 120, with 3 replications. Parameters observed are flowering date, harvesting date, plant height, height of dichotomous, stem diameter, crown width, fruit length, fruit diameter, fruit stalk length, weight per fruit and weight per plant. Results showed that genotype IPB C- 159 x IPB C- 120 has higher value on length of fruit and fruit stalk length compared than 3 tested genotypes. While the genotype IPB C- 159 x IPB C- 5 has higher value on fruit diameter, weight per fruit and weight per plant 3 other genotypes. Character flowering date, fruit length, fruit stalk length and weight of fruit is recommended as selection criteria for peatlands because it has a wide genetic variability and high heritability.   Keywords : Chili, inheritance, genetic variability, heritability, peatlands.